Exploiting spatio‐temporal knowledge for video action recognition - Huigang Zhang; Liuan Wang; Jun Sun (IET Computer Vision, 2023)
Abstract Action recognition has been a popular area of computer vision research in recent years. The goal of this task is to recognise human actions in video frames. Most existing methods often depend on the visual features and their relationships inside the videos. The extracted features only represent the visual information of the current video itself and cannot represent the general knowledge of particular actions beyond the video. Thus, there are some deviations in these features, and the recognition performance still requires improvement. In this sudy, we present a novel spatio‐temporal knowledge module (STKM) to endow the current methods with commonsense knowledge. To this end, we first collect hybrid external knowledge from universal fields, which contains both visual and semantic information. Then graph convolution networks (GCN) are used to represent and aggregate this knowledge. The GCNs involve (i) a spatial graph to capture spatial relations and (ii) a temporal graph to capture serial occurrence relations among actions. By integrating knowledge and visual features, we can get better recognition results. Experiments on AVA, UCF101‐24 and JHMDB datasets show the robustness and generalisation ability of STKM. The results report a new state‐of‐the‐art 32.0 mAP on AVA v2.1. On UCF101‐24 and JHMDB datasets, our method also improves by 1.5 AP and 2.6 AP, respectively, over the baseline method.